Expanding a Professional Learning Community to Focus on Inclusion, Belonging, and Student Success - Carroll, Heather; Pecoskie-Schweir, Sarah; Maher, Patrick T. (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2023)
Student success, particularly for students from marginalized populations, depends on a number of co-existing factors, not the least of which are a sense of belonging and the institution’s focus on inclusion. This article showcases the lessons learned from a professional learning community (PLC) for faculty, staff, and students, which was intentionally designed to create awareness of these issues and the need for courageous conversations to support change. The article discusses one particular PLC, a form of virtual “book club,” which occurred during the Fall 2021 semester (September–December). This PLC was focused on Anthony Jack’s text The Privileged Poor: How Elite Colleges Are Failing Disadvantaged Students, published in 2019, and encouraged a unique dialogue on student experience, co-facilitated by a team who critiqued aspects such as race, class, and first-generation status from different vantage points in higher education.